Demokrasi dalam Krisis Partisipasi: Perlukah Membangun Pendidikan Kebijakan Publik dan Hukum untuk Generasi Muda? - Putri, Rizky (Asosiasi Ilmuwan Administrasi Negara (AsIAN), 2025)
Indonesian democracy currently faces serious challenges in the aspect of meaningful public participation. Amid the availability of procedural participation space through elections and consultation forums, in reality public participation is often pseudo, people are involved symbolically without adequate understanding, access to information, or critical capacity. One of the main factors at the root of this problem is the lack of an inclusive, structured, and easily accessible public policy and legal education system for young people. In fact, Law Number 40 of 2009 concerning Youth firmly affirms the position of young people as strategic actors in national development, including their role as agents of social control in the process of formulating public policy. Policy and legal education is still concentrated in formal and professional academic environments, while the younger generation outside the lecture hall has minimal access to learn and be involved in the legislative process and public policy. With an exploratory-conceptual approach based on secondary data and scientific literature, this study reflects the urgency of inclusive policy literacy as a foundation for substantive participation. The findings and analysis in this study are expected to contribute to the development of alternative educational designs that bridge politics, public administration, and law, as well as being an initial reference for policy makers and education administrators in strengthening participatory democratic governance in Indonesia.